2021
DOI: 10.31223/x5t891
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal dispersal of fjord meltwaters as an important source of iron to coastal Antarctic phytoplankton

Abstract: This paper is a non-peer reviewed preprint submitted to EarthArXiv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 87 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…The Mn data are also contrasted with Fe data from the same transects, which was first presented in our previous work (van Genuchten et al, 2021), and evaluated in view of other reported Mn datasets in similar geographic environments around Greenland (Aciego et al, 2015;Hawkings et al, 2020;Achterberg et al, 2021;Krisch et al, 2021). These results provide insights into the biogeochemical behaviour of glacially-derived Mn and may help refine predictions concerning future changes to the relative availabilities of Fe and Mn in glaciated coastal regions (Browning et al, 2021;Forsch et al, 2021).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The Mn data are also contrasted with Fe data from the same transects, which was first presented in our previous work (van Genuchten et al, 2021), and evaluated in view of other reported Mn datasets in similar geographic environments around Greenland (Aciego et al, 2015;Hawkings et al, 2020;Achterberg et al, 2021;Krisch et al, 2021). These results provide insights into the biogeochemical behaviour of glacially-derived Mn and may help refine predictions concerning future changes to the relative availabilities of Fe and Mn in glaciated coastal regions (Browning et al, 2021;Forsch et al, 2021).…”
Section: Introductionmentioning
confidence: 88%
“…Although atmospheric particle fluxes are a major trace metal source to oceans on a global scale (Boyd and Ellwood, 2010), recent work suggests particle-rich glacier meltwater and the associated shelf sediments can be significant regional sources of Mn and Fe along glaciated coastlines (Wehrmann et al, 2014;Hawkings et al, 2020;Forsch et al, 2021). Glacially-derived metal fluxes are expected to be particularly prominent in glaciated fjords, such as along the coastline of West Greenland, where meltwater is confined, creating strong gradients in turbidity and salinity (Hopwood et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that both, abiotic as well as biotic terrestrial iron redox cycling are ultimately regulated and intensified by SWW-variations with important implications for the regional organic carbon (OC) www.nature.com/scientificreports/ budgets and micronutrient liberation. Climate as the main driver regulates differences in crystallinity, and thus, the bio-availability of the delivered Fe-phases 12,66,67 , strongly affecting runoff composition and, consequently, the marine primary productivity in adjacent fjords from seasonal to decadal time scales 18,19,68 . In this context, we assign particular importance to the continuous formation of noncrystalline RAMPs (Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Such noncrystalline, high-surface-area Fe-(hydr)oxides (e.g., ferrihydrite) stabilize coprecipitated OM and protect it from biodegradation under reducing conditions 12,42,43 . Unlike crystalline Fe-(hydr)oxides, these OM-associated noncrystalline Fe 2+/3+ -RAMPs and ferrihydrite coprecipitates should account to a great degree for terrestrial carbon sequestration 42,43 and the provision of bio-available iron for fjord primary productivity 66,67 . In contrast, the precipitation of hematite would increase iron fixation at www.nature.com/scientificreports/ the soil redox inter-face.…”
Section: Discussionmentioning
confidence: 99%